Rheological properties of asphalt binders with chemical tensoactive additives used in Warm Mix Asphalts (WMAs) - Morea, Francisco (2012)
Warm Mix Asphalts (WMAs) have been developed with the objective of minimizing the CO 2 emissions in the production and placement process of Hot Mix Asphalts (HMAs) by reducing temperatures at which these are mixed and compacted. However, this reduction must not affect the manufacturability and final performance of the mixture. WMA additives allow reducing the production temperature while maintaining mixture workability during the mix process and without compromising the final performance of concrete asphalt. There are different additives, some of which modify the rheological behavior of asphalts (wax or paraffin) while others, in theory, allow for unaffected rheological behavior (chemical additives). In this work the differences between the rheological properties of conventional and polymer modified asphalts, with and without chemical tensoactive additives, obtained from HMA and WMA, were studied by a Dynamic Shear Rheometer (DSR). Additionally, rutting resistance and moisture susceptibility were evaluated in these mixtures. The rheological properties of polymer modified asphalt were affected by the WMA additives, while in the conventional asphalt the rheological properties were not significantly affected. The WMA additives improved the workability of the mixtures in the production process. Performance improvements in the submerged wheel-tracking test were observed for WMA when additives were used, yielding results similar to HMA.